IMPLEMENTING MULTICULTURAL EDUCATION APPROACH IN PRE-SERVICE ELEMENTARY SCHOOL - Zariul Antosa (Universitas Muhammadiyah Ponorogo, 2018)
Multicultural approach is learning to use cultural diversity as a force in carrying out classroom learning. The aim of this research is to analyze the improvement of students' learning outcomes of art concepts between those who obtain learning with a multicultural approach and those who obtain conventional learning. This research is a quasi-experiment study with the nonequivalent control group design method for pre-service elementary school teacher. The research data were analyzed utilized the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results was in the experimental class obtaining an initial test average of 61.13 increased to 78.35 in the final test. While the control class obtained an initial test average of 61.65 and increased to 68.87 in the final test. The results of this research indicate that there are differences in the average score of the initial and final tests, but there is no statistically significant difference in the improvement of learning outcomes of the art concept between students who obtain learning through the application of a multicultural approach with students who are learning as generally.